The Reaction of Patients to Back Pain - Regina Lorencowicz; Józef Jasik; Marlena Kołodyńska; Krzysztof Turowski (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Back pain is an increasing health problem that significantly affects the feasibility of life goals of the individual. Back problems are the second most common cause of physical disability and absenteeism at work. Aim. Analysis of the most common reaction to the appearance of chronic pain in the population diagnosed with back pain syndrome. Material and Methods. The study included 187 patients diagnosed with back pain syndrome at the age from 20 to 83 years. The study was conducted in April and May 2013. A diagnostic survey method was used — the statistical analysis. The results were compared with studies nationwide that held a group of scientists under the direction of prof. J. Czapiński within the framework of the project “Social Diagnosis 2013 Conditions and Quality of Life Poles”. Results. The study showed that the average duration of back pain in the study group was 14.93±9.11 years (from 1 to 40 years). Average time elapsed since diagnosis was 8.34±6.24 years (from 1 to 25 years). 80.75% of respondents received assistance from the family doctor, 80.21% conducted X-ray, 28.34% CT and MRI of the spine 29.5%, 40.73% were diagnosed with neurological consultation. 85.56% of respondents performed work increased back pain, 80.75% preferred the systematic physical activity, 19.25% rested passively more than two hours a day or more, 56.15% did not cope with stress, 24.06% was dependent on nicotine. Conclusions. 1. Back pain occasionally prompts respondents to resort to professional help. 2. 22.9% of all households used hospital treatments, while among those diagnosed with spinal pain syndrome only 16.04% has decided on this form of therapy. 3. Back pain has prompted the majority (80.75%) of respondents to a systematic physical activity. 4. People diagnosed with spinal pain syndrome spend significantly less time on passive leisure than individuals from the general population. 5. The share of smokers in the group of patients diagnosed with spinal pain syndrome is 24.06%, which is comparable with the percentage of smokers in the general population of Poles (25.8%). (JNNN 2014;3(1):4–9)